Thoracopagus parasiticus, Hermophrodite Monster in a Gir Cow - DALAL, P S; DATTA, K S; MURTHY, K S (The Indian Journal of Animal Reproduction, 2023)
Incidence of monsters in cattle is one in 100,000 bovine births (Roberts, 1971 ). Of interest in this case report is the still birth of Thoracopagus Parasiticus hermophrodite monster with different external and internal anomalies. A seven year old cow (Kaveri, B.No.8 / 88) of the farm in 5th parity was reported to be straining for the last four hours after the. expulsion of first water bag. Rectal examination evealed ventral resentation in ventro-sacral position misleading to the presence of dead twins. The position was corrected per vaginally and the dystocia was relieved with traction and pulling the dead calf.